Kerjasama Kepolisian Indonesia Dengan Kepolisian Australia Dalam Menangani Imigran Gelap Asia Selatan Melalui Perairan Sukabumi Ke Pulau Christmas - Asma, Taswiah; Finaldin, Tom (Media Hukum Indonesia (MHI), 2025)
The prevalence of transnational crimes, especially illegal immigration in the Indonesian and Australian border regions, is an important issue requiring cooperation across countries. This study examines the collaboration between the Police and the Australian Federal Police (AFP) in handling dark immigrants of South Asian origin, such as those from Bangladesh and India, who attempt to enter Australia through Sukabumi waters towards Christmas Island. One significant case occurred on June 29, 2024, when 28 WNAs were found stranded in Sukabumi. The Indonesian government responded by strengthening policies through Immigration Law No. 6 Year 2011. With a qualitative descriptive method, this study reveals that increased cooperation between both policing plays an important role in strengthening bilateral relations, improving law enforcement systems, and maintaining maritime security in order to prevent the entry of illegal immigrants. Findings suggest that cross-state coordination and a strong legal foundation are crucial in confronting the challenges of dark immigration in this precinct.